2009
DOI: 10.1523/jneurosci.6096-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A/Hypocretin-1 Selectively Promotes Motivation for Positive Reinforcers

Abstract: Orexin A/hypocretin-1 (oxA/hcrt-1) is known to be a modulator of dopamine-dependent neuronal activity and behaviors. However, the role of this system in driving motivated behaviors remains poorly understood. Here, we show that orexin/hypocretin receptor-1 (ox/hcrt-1R) signaling is important for motivation for highly salient, positive reinforcement. Blockade of ox/hcrt-1R selectively reduced work to self-administer cocaine or high fat food pellets. Moreover, oxA/hcrt-1 strengthened presynaptic glutamatergic inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
335
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(390 citation statements)
references
References 57 publications
40
335
2
2
Order By: Relevance
“…These results appear to be at variance with those that have demonstrated the absence of intra-VTA SB334867 on cocaine self-administration in low-effort fixed ratio 1 (FR1) schedules of reinforcement (40). However, several reports have shown that as task demands increase, SB334867 is more effective in reducing drug taking (2,33). Because rats in this experiment were performing a higher effort FR5 schedule, the present findings are consistent with this literature.…”
Section: Orexin and Dynorphin Can Exert Balanced Opposing Effects Onsupporting
confidence: 82%
See 1 more Smart Citation
“…These results appear to be at variance with those that have demonstrated the absence of intra-VTA SB334867 on cocaine self-administration in low-effort fixed ratio 1 (FR1) schedules of reinforcement (40). However, several reports have shown that as task demands increase, SB334867 is more effective in reducing drug taking (2,33). Because rats in this experiment were performing a higher effort FR5 schedule, the present findings are consistent with this literature.…”
Section: Orexin and Dynorphin Can Exert Balanced Opposing Effects Onsupporting
confidence: 82%
“…addiction | kappa-opioid receptor | mood | neurotransmission | stress O rexin promotes arousal (1) and has been implicated in the rewarding effects of food (2,3), sexual behavior (4), and drugs of abuse (5,6). It is produced primarily within the hypothalamus (7), and acts at orexin 1 receptor (OX 1 R) and OX 2 R (also known as Hcrt-R1 and Hcrt-R2), which are expressed in many brain areas, including the ventral tegmental area (VTA) of the midbrain (8).…”
mentioning
confidence: 99%
“…It is possible that a more extensive depletion may be required in order to reveal an effect on the incentive value of food Another potentially important factor is the level of food deprivation. The subjects of this experiment were maintained at 80% of their free-feeding body weights, whereas most previous studies of the effect of manipulating orexinergic function on motivated behaviour have been carried out on non-deprived animals or under milder deprivation conditions than that used in this experiment Harris and Aston-Jones, 2006;Borgland et al, 2009;Cason et al, 2010;Sharf et al, 2010). It is not clear how this might have influenced the results, although the control of food intake is known to be different in nondeprived and deprived states (Rowland et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of the hypocretin system in the rewarding properties of cocaine has mainly been revealed under conditions that require greater degrees of effort and motivation to obtain the drug (28,29). The present data point to a specific role for Hcrtr-1 in the modulation of the reinforcing properties of cannabinoids since the Hcrtr-2 antagonist TCSOX229 did not alter this behavior.…”
Section: The Enhanced Of Dopamine Extracellular Levels In the Nucleusmentioning
confidence: 50%
“…VTA hypocretin signaling seems to be particularly important in the regulation of drug reward seeking behavior (42). Thus, the VTA shows high density of hcrtr-1 (28,43), hypocretin-1 induces a direct depolarization of VTA dopamine neurons (44), and the intra-VTA infusion of hypocretin-1 increases dopamine levels in the NAc (43,45). Although the exact neuronal mechanism is unclear at present, our findings suggest that cannabinoid exposure could induce the release of hypocretins in the VTA following the activation of these neurons in the LH, which directly project to the VTA (46).…”
Section: The Enhanced Of Dopamine Extracellular Levels In the Nucleusmentioning
confidence: 99%